The Effect of Change Management, Training and Work Life Balance on Employee Performance at the Regional Personnel and Human Resources Development Agency of Pangkalpinang City - Putri, Vheditya; Reniati, Reniati; Wahyudin, Nanang (International Journal of Economics, Business, and Entrepreneurship, 2023)
This study aims to determine whether there is an effect of change management, training and work life balance on employee performance. The population inthis study were all employees at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Daerah Kota Pangkalpinang by sampling with the saturated sample method. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis tests, t tests, f tests, and R2 tests using the Statistical Package for Social Science (SPSS) version 24. Based on descriptive analysis on the variables of change management and work life balance are in the very high category, and training is in the high category. Based on multiple linear regression analysis shows that Change Management, Training, Work Life Balance partially and simultaneously have a positive and significant effect on employee performance. The results of the analysis of the coefficient of determination (R2) with Adjusted R Square of 0.74 or 74%. It states that the variable of employee performance is influenced by the variables of management, training, and work-life balance by 74%, the remaining 26% is influenced by other variables from the research variables.